Form-stable phase change composites with high thermal conductivity and electrical insulation. (1st August 2022) - Zhang, Huaqing; Zhang, Shixian; Li, Chenjian; Shi, Zhuqun; Yang, Quanling; Wang, Shan; Xiong, Chuanxi
Abstract: The commercialization of phase change materials (PCMs) based on paraffin is obstructed by the drawbacks of leakage and low thermal conductivity. Herein, we developed form-stable phase change composites via trapping paraffin into triblock copolymer. The hybrid filler, namely boron nitride and Ag-coated hollow glass microspheres (Ag@HGMs), was introduced to enhance the thermal conductivity of the composites. The latent heat values of composites could be easily tailored in a range of 157.6–192.4 J g −1 by changing the loading of filler. Interestingly, the addition of boron nitride and Ag@HGMs hybrid filler has little impact on electrical insulation property, and displays a synergistic effect on the heat transfer improvement within the composites. The sample BN/Ag@HGMs-4 exhibits excellent latent heat, electrical insulation performance, thermal recycling properties and stability, and the thermal conductivity reaches up to 1.54 W m −1  K −1, which has great potential application in thermal management and heat energy collection system. Highlights: The Ag@HGMs were fabricated via an improved electroless silver plating method. Paraffin/SEBS//boron nitride/Ag@HGMs phase change composites (PCCs) were prepared. The improvement in thermal conductivity of PCCs was achieved. The addition of hybrid filler ensures the excellent electrical insulation property.